Capitalism Effects through Asian Crisis: An Analysis of South Korea's Economic Policy in the Welfare State Perspective - Hyung-jun, Kim; Peng, Li; Kaita, Murayama (Pancasila International Journal of Applied Social Science, 2023)
The Asian financial crisis with a marked fall in the value of the Thai currency (Bath), initially a currency crisis was followed by a financial crisis in non-bank financial institutions which had to be closed due to bankruptcy. The economic crisis was followed and spread to South Korea, Malaysia, Indonesia, the Philippines, Singapore and other Asian countries. International institutions reacted to help with the Asian crisis, initially The International Monetary Fund (IMF) after being asked for assistance by Asian countries provided assistance. Many analyzes have been given by financial, economic and political experts, one of which is Weiss and Hobson who analyzed that the Asian economic crisis appeared to have two faces namely; the external face is in the Deep Crisis area and the external face is in the ordinary crisis area, while the crisis occurs from the role of international actors, both state and non-state actors. The social policy approach that is applied takes welfare state steps, with welfare programs implemented by South Korea including reforms in the fields of labor, market and finance, BUMN and active social policies to provide social security for the unemployed or for those who become poor in the period of national economic reform. Weiss and Hobson concluded that state guided capitalism was one of the causes of the Asian crisis.